(untitled) (Research, Society and Development, 2021)
Raízen is a global reference in bioenergy, a protagonist in the energy transition and stands out in the search for redefining the future of energy. In this article, the circular economy model applied to this company will be addressed, which aims at a more efficient management of existing natural resources, that is, to maintain products, components and materials at their highest level of utility and value at all times, within an economic scope of sustainable development. The on-screen study aims to discuss how the company realizes synergies by seeking an efficient circular economy model, analyze the practices disclosed in the circular economy model and the potential factors that influence them, identify practical opportunities, solutions and the barriers encountered, based on an understanding of the circular economy model and the advances it reveals towards achieving sustainability. It is expected to contribute with future works in this area, by enabling a more objective and real look at the subject, given its relevance and in the sense of contributing to the achievement of sustainable development.